PENERAPAN AUGMENTED REALITY DALAM PENGENALAN PERALATAN MANUFAKTUR PADA PRODI TEKNIK INDUSTRI UNIVERSITAS UNIVERSAL - Kaharuddin Kaharuddin; Musliadi KH; Kurniawan Hamidi; Ilwan Syafrinal (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
An effective learning process to produce quality education requires supporting facilities such as adequate practicum media, Industrial Engineering Universal University currently has limitations with practicum media, especially in the introduction of industrial engineering manufacturing tools, therefore alternative media such as AR technology are needed. The purpose of this study is to determine the effectiveness of learning and the overall quality of education from the application of AR-based applications. The application of this technology can be developed using the Game Development Life Cycle (GDLC) method through several stages. The development results were randomly tested on 40 respondents by applying three indicator features and five statements used and obtained presentation values ranging from 78% to 81% user satisfaction before the application with strong presentation. While from the results of the analysis carried out on each indicator used, the first stage with the highest percentage is Usability, followed by functional indicators and user interface indicators at the lowest percent.